Pursuing strategy NATO operations from the Gulf War to Gaddafi - Edstrom, Hakan; Gyllensporre, Dennis (New security challenges series, 2012)
Formulating a strategy involves complex interactions between politicians, strategic commanders and generals in the field. The authors explore the strategic decisions made during NATO missions in Bosnia-Herzegovina, Kosovo, Macedonia, Afghanistan, Somalia and Libya. They reveal that it is a misconception that overall strategies radiate solely from political leaders. Instead, military officers at an operational level can achieve change as General McChrystal did for Afghanistan in 2009. The authors conclude that NATO cannot succeed in complex operations without the political support for these bottom-up initiatives.